Dark/light transition and vigilance states modulate jaw-closing muscle activity level in mice. (December 2015) - Katayama, Keisuke; Mochizuki, Ayako; Kato, Takafumi; Ikeda, Minako; Ikawa, Yasuha; Nakamura, Shiro; Nakayama, Kiyomi; Wakabayashi, Noriyuki; Baba, Kazuyoshi; Inoue, Tomio
Highlights: Sleep/wake state largely modulates the activities of the masseter and neck muscles. Dark/light transition modulates the activities of the two muscles to a lesser degree. Even during non-REM sleep, the masseter muscle displays bimodal activation. Bimodal masseter activation may contribute to exaggerated activity in sleep bruxism. Abstract: Bruxism is associated with an increase in the activity of the jaw-closing muscles during sleep and wakefulness. However, the changes in jaw-closing muscle activity across states of vigilance over a 24-h period are unclear. In this study, we investigated the effects of dark/light transition and sleep/wake state on EMG activity of the masseter (jaw-closing) muscle in comparison with the activity of the upper trapezius muscle (a neck muscle) over a 24-h period in mice. The activities of the masseter and neck muscles during wakefulness were much greater than during non-REM and REM sleep. In contrast, the activities of both muscles slightly, but significantly, decreased during the transition period from dark to light. Histograms of masseter activity during wakefulness and non-REM sleep showed bimodal distributions, whereas the neck muscle showed unimodal activation in all states. These results suggest that the activities of jaw-closing and neck muscles are modulated by both sleep/wake state and dark/light transition, with the latter being to a lesser degree. Furthermore, even during non-REM sleep, jaw-closing muscles display bimodal activation, which may contribute to the occurrence of exaggerated aberrant muscle activity, such as sleep bruxism.